Determinan Bekerja Tidak Penuh di Indonesia - Nikhen Pratiwi Sekar Tanjung (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2018)
This study is intended to find out the profile of part-time workers and the factors which affecting part-time workers in Indonesia with Sakernas Agustus 2016. Part-time workers are female, living in the rural areas, 35-44 years old, married, have less of human capital, non-disabilities persons, do not have household members under 10 years old, works in the agricultural sector, unpaid workers, informal sector, and monthly wages less than 500 thousand rupiahs. The results of binary logistic regression analysis showed that female workers, living in rural areas, aged above 55, unmarried, low-educated persons, never attending job training, having work experience, disabled-persons, having household members under 10 years old, and working in agricultural sectors have greater opportunity to become part-time workers in Indonesia.